PELATIHAN PENINGKATAN KUALITAS DAN FASILITASI UJI TEKAN BATU BATA MERAH DI KAMPUNG DURUNG KIDUL, BOJONG, NAGREG JAWA BARAT - Intan Rahmatillah; Yoanita Yuniati; Yuniar Yuniar; Andrean Maulana; Sely Putri (LP4MK STKIP PGRI Lubuklinggau, 2020)
Redbrick craftsmen can be found in various regions in West Java, one of which is in the area of ​​Kampung Durung Kidul Bojong Nagreg. The skills of craftsmen making bricks in the area are passed down from generation to generation. The process of making red bricks is carried out simply by utilizing the clay in the surrounding environment which is mixed then molded and burned using husks. The results of observations and interviews identified that the understanding of the craftsmen to improve the quality and understanding of the importance of brick products by SNI standards was still lacking. Based on this, in this activity, counseling was carried out on the SNI standard for red bricks and facilitated the craftsmen to test the red brick products, especially with the test of pressure tests. The test results showed that the compressive strength of 45 samples ranged from 6.75 - 14.616 N / mm2, with the quality category according to the SNI 15-2094-2000 standard being class II and class III. This shows that the craftsmen in Bojong Village need to be helped to improve the quality of their brick products. Community service activities provide a plan for improving the quality of the red bricks that craftsmen need to do.